(untitled) (Applied Biological Research, 2020)
A study was conducted to assess the impact of soil agro-techniques and rootstocks on new apple plantation at an old declining apple orchard site. The study comprised of 20 treatments viz., four apple rootstocks namely Seedling, Merton 793, MM.111 and M.7, and five soil agro-techniques i.e. soil fumigation with formaldehyde, PGPR (Bacillus licheniformis CK-1), biocontrol (Trichoderma viride), combined agro-techniques and untreated control. The rootstock of ‘Merton 793’, combined soil agro-techniques and their combination showed higher growth (height, leaf area, feathers and plant volume) and improved physiological activities (chlorophyll content, photosynthetic efficiency and chlorophyll fluorescence) as compared to the other rootstocks and untreated control under replant situations. These approaches can be effectively adopted to overcome the replant problem in apple orchards.